2016
DOI: 10.17305/bjbms.2016.982
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of hypertransaminasemia in Turkish children

Abstract: The aim of this study was to investigate the causes of elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in children. We analyzed the medical records for children aged 3 months to 18 years who presented to the hospital with ALT >45 IU/L and/or AST >50 IU/L, between 2012 and 2014, for various reasons, including those not related to liver disease. In total, 281 children met the study criteria. This group comprised of 125 (44.5%) females and 156 (55.5%) males. At the presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 26 publications
1
22
0
3
Order By: Relevance
“…Studies from Asia or Australia were published in more recent years. Majority of the studies included adult populations (62%), two studies (7%) included children aged 18 years and below, eight studies (28%) included a mixed adult and children population, while age limit was not reported in one study . Apart from two prospective studies with shorter study periods, the rest of the studies were conducted retrospectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from Asia or Australia were published in more recent years. Majority of the studies included adult populations (62%), two studies (7%) included children aged 18 years and below, eight studies (28%) included a mixed adult and children population, while age limit was not reported in one study . Apart from two prospective studies with shorter study periods, the rest of the studies were conducted retrospectively.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to reporting quality, selection criteria and detection algorithm were generally well‐reported, with the exception of two studies which did not list out the specific diagnosis codes. Eleven studies did not report the expertise of adjudicators in confirming the DILI cases. Only seven studies performed well in generalizability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBZ is potent inducer of AST, ALT and GGT, as well. The elevation of serum levels of AST, ALT and GGT, without any signs and symptoms of liver injury can be explained as a result of enzyme induction, without hepatic patology ( 7 ). Valproate (VPA) has very complicated biotransformation.…”
Section: Discussionmentioning
confidence: 99%
“…In asymptomatic patients, the most frequent causes of elevated transaminases were drug induced liver injuries. The elevation can be secondary to enzyme induction, without hepatic pathology ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%